Architecture Typology of Rural Plain Houses Based on Formal Features, Case Study: (Talesh, Iran) - Ghanbari, Sousan; Yeganeh, Mansour; Reza bemanian, Mohammad (Frontiers in Built Environment, 2022)
Housing is the most essential human need that in the past, rural houses have met this need well. Indigenous rural homes have undergone changes over time, some of which have been based on internal needs and needs, and some have been due to development and exogenous changes. One of the most critical steps to identify this type of change is the typology of indigenous homes; In this way, an essential step in the path of cognition, understanding and more coverage of this phenomenon is taken. Based on this, the present study intends to study and analyze the architectural types of houses in Talesh village, which originate from human nature, natural space and the bed in which they are formed. Therefore, to estimate the proportions and classification of the architectural plans of its houses, it is necessary to use a quantitative-qualitative research method. Mathematics is used in the Python programming language in data analysis. For this purpose, by selecting 150 samples of rural houses in the form of purposeful clusters and converting the created matrix from the dimensions and size of the plans to zero and one code, their similarity has been calculated. They are in close categories. Findings obtained by simulating the plans show that sloping roofs, building elevation, east-west orientation, porch, open plan and natural ventilation are common features in all indigenous houses. It is found in this area. Therefore, in general, the two architectural patterns in this area are one-story houses and Telar houses, in which high chair houses are a frequent type.